Respuesta :

Explanation

  • Separate the constant out of expression.

[tex]( {n}^{2} - 6n) + 6 = - 2[/tex]

  • Find the constant that makes the expression able to be squared. You have to subtract the separated constant by new constant as well.

[tex]( {n}^{2} - 6n + 9) + 6 - 9 = - 2 \\ {(n - 3)}^{2} - 3 = - 2 \\ {(n - 3)}^{2} = 1[/tex]

  • Square Root both sides to get rid the squared expression. Make sure to write plus or minus.

[tex] \sqrt{ {(n - 3)}^{2} } = + \sqrt{1} \\ \sqrt{ {(n - 3)}^{2} } = - \sqrt{1} \\ n - 3 = 1 \\ n - 3 = - 1[/tex]

[tex]n - 3 = 1 \: \: \: or \: \: \: n - 3 = - 1 \\ n = 1 + 3 \: \: \: or \: \: \: n = - 1 + 3 \\ n = 4 \: \: \: or \: \: \: n = 2[/tex]

Answer

[tex] \large \boxed {n = 4,2}[/tex]

ACCESS MORE